Keanekaragaman Budaya, Interaksi Multikultural, dan Dampaknya terhadap Perilaku Pencarian Kesehatan dan Kesejahteraan di Lingkungan Urban Bukit Bintang, Malaysia - Anggie Noer Apriliani; Syafri Anwar; Febriandi (Jurnal Penelitian Pendidikan IPA, 2026)
Cultural diversity and everyday multicultural interactions strongly influence health-seeking behavior and well-being in complex urban settings. Bukit Bintang is a cosmopolitan urban district in Malaysia where culturally diverse communities interact within shared spaces. This study aims to examine how cultural diversity and everyday multicultural encounters influence health-seeking behavior and well-being among residents and visitors within the Bukit Bintang urban environment. Employing a qualitative research design, this study draws data from literature reviews, national and international journal articles, research reports, interviews, observations, and contextual documentation. The researcher served as the primary instrument, supported by interview protocols, observation guidelines, recording tools, and field documents. The analysis focused on subjective meanings, lived experiences, and participants’ interpretations of cultural and health-related practices. Findings reveal that multicultural interactions affect health-seeking behavior through varying preferences for traditional and modern healthcare, reliance on culturally familiar providers, and differing levels of trust in formal health institutions. While diversity promotes inclusivity and enriches the social fabric, challenges remain, including communication barriers, socio-economic disparities, and uneven access to health information. The study concludes that culturally responsive health strategies and inclusive community engagement are essential to improving health equity and supporting well-being within Malaysia’s multicultural urban environments.